2017
DOI: 10.1021/acs.analchem.7b00008
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Droplet Microarray of Individually Addressable Electrochemical Cells

Abstract: Microarray technology has shown great potential for various types of high-throughput screening applications. The main read-out methods of most microarray platforms, however, are based on optical techniques, limiting the scope of potential applications of such powerful screening technology. Electrochemical methods possess numerous complementary advantages over optical detection methods, including its label-free nature, capability of quantitative monitoring of various reporter molecules, and the ability to not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…For example, the volume of microdroplet had been reported to be as low as picoliter and femtoliter, and the geometry of the (micro)reservoir can be tuned for the synthesis of materials with specific shapes, such as hydrogel particles, biofilm microcluster, metal organic framework microsheet, and nanoparticle assembly . 3) (Micro)reservoirs can be spatially close to each other because droplet coalesce is avoided, which paves the way for miniaturization and point‐of‐care application of the SPW . 4) SPW can be obtained by fabricating micro‐/nanostructures on various substrates, which can promote the wider applications of SPW based on the functions of different substrates …”
Section: Applicationsmentioning
confidence: 99%
“…For example, the volume of microdroplet had been reported to be as low as picoliter and femtoliter, and the geometry of the (micro)reservoir can be tuned for the synthesis of materials with specific shapes, such as hydrogel particles, biofilm microcluster, metal organic framework microsheet, and nanoparticle assembly . 3) (Micro)reservoirs can be spatially close to each other because droplet coalesce is avoided, which paves the way for miniaturization and point‐of‐care application of the SPW . 4) SPW can be obtained by fabricating micro‐/nanostructures on various substrates, which can promote the wider applications of SPW based on the functions of different substrates …”
Section: Applicationsmentioning
confidence: 99%
“…Reproduced with permission. 117 Copyright 2017, American Chemical Society bioinspired surface, detections of adenine, dopamine (DA), glucose, and DA and methyl blue (MB) with high sensitivity and mutually independent multi-sample were realized even without interference ( Figure 6E,F). By self-assembly and photocatalytic lithography, 111 Lai et al fabricated superhydrophilic/superhydrophobic patterns with erasable and rewritable properties on a TiO 2 nanotube array (TNA) sample, whereby the site-selective cell immobilization and reversible protein absorption were conducted on 2D scaffold TNA surface.…”
Section: F I G U R E 7 (A B) Fabrication Processes To the Electrochementioning
confidence: 99%
“…Several chip devices have been proposed for detection, such as integrated electrode arrays 72 and microfluidics. 73 Misun et al reported a droplet array device with enzyme-modified electrodes for body-on-a-chip applications (Fig.…”
Section: Droplet Detection Containing 3d Cultured Cellsmentioning
confidence: 99%